Histoire sociologique du droit de la chasse et de la peche en Ontario - Ribordy, François-Xavier (Anthropologica, 2022)
The history of hunting regulations in Ontario represents a continuation of eighteenth century English law. In that country hunting was a sport and a privilege of the landowning aristocracy. These laws proved very unsuitable to Canada where private ownership of land was very limited, and both Indians and colonists were obliged to hunt in order to survive. Towards the end of the nineteenth century, the extensive destruction of game caused by the growth of railways, mining, forest exploitation and American industrialization compelled the government of Ontario to take preventive action. These measures included prohibitions against hunting certain animals, the institution of game commissions, the hiring of game wardens and the introduction of compulsory hunting licenses. Although it furnishes valuable natural resources, for some considerable time hunting had a very low profile vis-a-vis mining, forestry and commercial fishing. Nonetheless, the government eventually realized that, properly regulated, hunting could be not only a pleasant, open-air sport, but a source of considerable revenue for the provincial coffers. From that time on it became clear that properly managed game reserves would attract tourists, especially Americans. This new orientation provoked a considerable change in the philosophy which was embraced by natural resource managers and which sustained the hunting laws. That philosophy was no longer preoccupied with the prevention of poaching but rather with biological and ecological concerns and the education of the public. However, the transition from anti-poaching laws and police actions to biological conservation measures has not